Pengaruh BOPO, NPF, FDR Terhadap Profitabilitas Bank Muamalat Indonesia Tahun 2013 – 2022 - Surya Tegar Widjiantoro (ITB AAS INDONESIA Surakarta, 2023)
This research is using secondary data quantitative methods obtained from various trusted sites such as OJK, BPS, Muamalat etc. This study uses data from 2013 to 2022. This study uses multiple regression analysis method with 3 (three) variables X and 1 (one) variable Y. This study seeks the influence contained in each research variable. The results of this study are the BOPO variable has a significant negative effect on the ROA variable, this can be proven by t count > t table (11.935 > 1.860) and Sig value < α (0.000 < 0.05) and the NPF, FDR variables do not have a significant effect on ROA. This can be proven by each calculation t count < t table (0.603 < 1.860) and Sig value > α (0.573 > 0.05) for NPF and t count < t table (0.558 < 1.860) and Sig value > α (0.601 > 0.05) for FDR.